Paramilitaries, Peace Processes and the Dilemma of Protection: The Ulster Defence Association's Role in 'Keeping a Lid on Loyalism'. (August 2013) - Mitchell, Audra; Templer, Sara
Paramilitary actors involved in peace processes are expected to contribute to two distinct forms of protection: national-level protection as 'security'; and local-level security as 'safety'. Examining the case of the Ulster Defence Association (UDA) in Northern Ireland, we explain how these two forms of protection have become interlinked in the Good Friday/Belfast Agreement (GF/BA) and the related peace process. Instead of generating a virtuous cycle, this has created a dilemma between providing protection as 'safety' and as 'security'. Drawing on interviews with key UDA-affiliated actors in 2009–10, against the backdrop of increasing 'dissident Republican' violence, we assess how they navigated this dilemma, and its potential effects on the unfolding political context, calling for greater attention to the relationship between different conceptions of protection in peace processes.